2017
DOI: 10.3390/ijerph14010079
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Emerging Micropollutants in Water Systems in Gauteng, Mpumalanga, and North West Provinces, South Africa

Abstract: The ubiquitous occurrence of emerging micropollutants (EMPs) in water is an issue of growing environmental-health concern worldwide. However, there remains a paucity of data regarding their levels and occurrence in water. This study determined the occurrence of EMPs namely: carbamazepine (CBZ), galaxolide (HHCB), caffeine (CAF), tonalide (AHTN), 4-nonylphenol (NP), and bisphenol A (BPA) in water from Gauteng, Mpumalanga, and North West provinces, South Africa using comprehensive two-dimensional gas chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 58 publications
0
39
0
Order By: Relevance
“…When the Gaborone reservoir was completed in 1984, the Ramotswa groundwater was no longer piped to Gaborone and was only used to supply Ramotswa. In 1996, the Ramotswa wellfield was abandoned because NO 3 − concentrations exceeded the national drinking w a t e r s t a n d a r d , 5 0 m g N O 3 − L − 1 o r 1 1 m g NO 3 − −N L −1 (Walmsley and Patel 2011), and because Ramotswa lacked the capacity to treat the water (Moehadu 2014). Water was therefore piped in from Gaborone (Fig.…”
Section: Water Supply and Treatment Infrastructurementioning
confidence: 99%
See 2 more Smart Citations
“…When the Gaborone reservoir was completed in 1984, the Ramotswa groundwater was no longer piped to Gaborone and was only used to supply Ramotswa. In 1996, the Ramotswa wellfield was abandoned because NO 3 − concentrations exceeded the national drinking w a t e r s t a n d a r d , 5 0 m g N O 3 − L − 1 o r 1 1 m g NO 3 − −N L −1 (Walmsley and Patel 2011), and because Ramotswa lacked the capacity to treat the water (Moehadu 2014). Water was therefore piped in from Gaborone (Fig.…”
Section: Water Supply and Treatment Infrastructurementioning
confidence: 99%
“…The maximum detection limit of 200 colony forming units (CFU) per 100 ml was observed at least once in BH4371, BH4995, and BH10129, indicating that actual concentrations could be higher. The Botswana drinking water standard is zero CFU per 100 ml (Walmsley and Patel 2011). The presence of fecal coliforms suggests that other fecal pathogens are likely to be present in the aquifer.…”
Section: Nitrate Source Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…Grahamstown treated effluents (GE) contained 23.50% of BPA unremoved, while Alice effluents (AE) had 18.34%. Wanda et al (2017) reported various concentrations of BPA in some South African rivers. BPA has been detected in rivers and wastewaters in many countries of the world such as India, China, Russia and several others and similarly its concentrations in wastewater effluents were reduced compared to influents (Corrales et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…During data acquisition, ultrapure water was analysed between replicates to check memory effects. Detection limit (LOD) of the dissolved Ag NPs was determined using Linear regression analysis [46]. The Ag nanoparticle diameter limit of detections (DLs) were determined by three times the standard deviation above the background when measuring ultrapure water [26,45].…”
Section: The Sp-icp-ms Analysismentioning
confidence: 99%